Ensiling as a Conservation Technique for Opuntia ficus indica (L.) By-Products: Peel and Pastazzo - Riccardo Gannuscio; Cinzia Cardamone; Alessandro Vastolo; Caterina Lucia; Angela D’Amico; Giuseppe Maniaci; Massimo Todaro (Animals)
Italy is the third largest producer of Opuntia fruits in the world after Mexico and the United States, and 97.72% of these fruits produced by Italy are grown in Sicily. The use of prickly pear fruits or juice leads to a high production of by-products. In this study, ensiling was chosen to preserve prickly pear peels (PPPs) and “pastazzo” (PPS) mixed with 12% wheat bran. PPP silage presented a lower DM than PPS silage (20.03 vs. 41.37%; p < 0.01), as well as aNDFom (25.31 vs. 66.66% DM; p < 0.01), but had the best protein content (12.02 vs. 9.55% DM; p < 0.01). For both by-products, fermentation proceeded rapidly with increasing temperature, with the temperature for PPS (38 °C) being higher than that for the PPP (30 °C). Mesophilic LAB (lactic acid bacteria) were detected at higher levels than thermophilic LAB, and rod counts were higher than cocci counts. The detected organic acids and silage pH indicate an optimal fermentation process for these by-products. PPP silage had a higher polyphenol content than PPS silage (30.24 vs. 24.22 mg GAE/g DM; p < 0.01) and, consequently, also higher antioxidant activity. The results of this study on the mineral composition and macro- and micro-nutrients in silage highlight that these by-products are sources of minerals, with high levels of potassium, calcium, and magnesium.